Optimalisasi Kepuasan Kerja Karyawan Berbasis Lingkungan Kerja Fisik dan Keselamatan Kerja di Bagian Produksi PT YXZ Subang - Fauzi, Rizky Nur; Romi, Mochamad Vrans (Universitas Batanghari, 2024)
Companies can strive to increase employee job satisfaction to achieve conditions that encourage optimal development and improvement of employee abilities. Work environment and safety in the workplace are some of the factors that affect employee job satisfaction. The attendance rate in the Production Department of PT YXZ continues to increase. This is due to poor physical working conditions and a lack of attention to occupational safety. The purpose of this study is to partially and simultaneously determine the effect of the physical work environment and work safety on employee job satisfaction in the production department of PT Â YXZ. The research method used is a quantitative method with data analysis using multiple regression analysis assisted by SPSS version 26. The data collection technique used was a questionnaire with 33 respondents, all employees of the Production Department YXZ. The results of this study show that the physical work environment partially affects employee job satisfaction, and work safety does not affect employee job satisfaction. While simultaneously the physical work environment and work safety affect employee job satisfaction, Employee satisfaction will increase with a good physical work environment and good work safety